Benefits of Early Treatment for Patients with Hepatic Myelopathy Secondary to TIPS: A Retrospective Study in Northern China. Issue 1 (December 2018) - Zhao, Hongwei; Yue, Zhendong; Wang, Lei; Fan, Zhenhua; He, Fuliang; Dong, Xiaoqun; Liu, Fuquan
Abstract Transjugular intrahepatic portosystemic shunt (TIPS) is an effective therapy for reducing portal pressure. Hepatic myelopathy (HM), a rare complication of chronic liver diseases, remains obscure in terms of treatment and prognosis. We aimed to determine an optimal treat strategy for patients with HM after TIPS. Twenty-nine patients who developed HM after TIPS were stratified by time-lapse from onset to treatment: group A (n = 16), <6 months; group B (n = 13), ≥6 months. Therapeutic measures included shunt-limiting and medical treatments. Overall survival, lower-limb muscle strength, Fugl-Meyer score, Barthel index, and serum ammonia were recorded. Median survival time in group A or B was 30 months or 16.5 months, respectively (log rank p = 0.0172). All patients in group A obtained improvement in grading of muscle strength (p < 0.0001), Fugl-Meyer score (p = 0.0021), and Barthel index (p = 0.0003), particularly male patients and those subjected to shunt-limiting. Serum ammonia levels were decreased significantly in both group A (p = 0.0007) and group B (p = 0.0007). Collectively, once HM is confirmed after TIPS, active intervention is imperative and urgent, especially within the first 6 months from onset of symptom. TIPS shunt-limiting is particularly beneficial for rehabilitation in patients with early-onset HM.